Truck - Llewellyn, Claire (London ; New York : Dorling Kindersley, 1995)
Takes a close-up look at many different trucks, including a dump truck, a forklift, and a bulldozer. Photographs and text reveal how these vehicles work and what they do.
"And other building machines"--Cover.
Wilson's Children.
Child Study Children's Book Committee.
4.0
K-3
Keywords: Trucks -- Juvenile literature; Earthmoving machinery -- Juvenile literature; Trucks; Earthmoving machinery; Trucks; Earthmoving machinery; Trucks; Earthmoving machinery